Harga Jual Beras melalui Perhitungan Harga Pokok Produksi dengan Metode Full Costing dan Variable Costing pada Penggilingan Padi Talago - Rahmatika; Ariani, Fatma (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2024)
This descriptive quantitative research was conducted to determine the selling price of rice through the calculation of the cost of goods manufactured. The data used consisted of primary data from interviews with the manager of the Talago Rice Mill. Data processing was carried out using the full costing and variable costing methods to determine the cost of goods manufactured. The results of the analysis and discussion show that the selling price of rice determined by the manager is lower than the selling price calculated by the full costing method and higher than the selling price by the variable costing method. The selling price obtained from the full costing method is IDR 16,200/kg, while the selling price using the variable costing method is IDR 15,400/kg. This price is different from the selling price determined by the manager as the producer, which is IDR 16,000/kg.